The second imprisonment of Paul: Fiction or reality? - Eurell, John-Christian (Scottish journal of theology, 2023)
This article examines the commonly held conception that Paul was released after his first Roman imprisonment, went to Spain and was eventually reimprisoned and executed in Rome. After examining the available evidence it is concluded that the theory of a release of a release and second imprisonment of Paul is ill founded.